The content of the preventive measure of home detention - Stanciu, Mihai-Alexandru (Technium Social Sciences Journal, 2021)
The criminal procedural provisions in Romania regulate a number of 5 preventive measures, of which 3 are custodial and two restrictive. Of these, the measure of house arrest, regulated as a novelty at the beginning of 2014, seems to be an intermediate form between judicial control and pre-trial detention, borrowing elements of content from both measures. Compared to the obligations that can be imposed on the defendant arrested at home, certain situations can be left uncovered by the legislator, which can make the measure seem ineffective in practice.